Peer review of the pesticide risk assessment of the active substance aluminium ammonium sulfate. (13th May 2022) - ,; Alvarez, Fernando; Arena, Maria; Auteri, Domenica; Binaglia, Marco; Castoldi, Anna Federica; Chiusolo, Arianna; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Ireland, and co‐rapporteur Member State, Portugal, for the pesticide active substance aluminium ammonium sulfate and the considerations as regards the inclusion of the substance in Annex IV of Regulation (EC) No 396/2005 are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of aluminium ammonium sulfate as a repellent on row crops (salad, brassica, carrots and other vegetable crops), combinable crops (grains, pulses and oilseed rape), grassland (primarily amenity and sports turf), orchards and forestry, amenity and ornamentals including use on hard surfaces. The reliable end points, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework and assessments not finalised are listed.